Maintenance and Supply of Post and Telegraph Stations in the Semirechye - Iskakova, Galiya Z; Teleuova, Elmira T. (Journal of Ecohumanism, 2024)
The article explores the material supply of post and telegraph stations in the Semirechye region during the late 19th and early 20th centuries. The management of postal routes, transport safety, and the construction and equipment of stations were determined by the state, private entrepreneurs, and the local Kazakh population, who were taxed for these services. In addressing these challenges, the Russian Empire drew from European experiences, directly applying the postal station management model from Russia. Postal routes facilitated the transportation of correspondence, cargo, and passengers, thus solving essential communication issues within society. Government officials and soldiers also relied on these stations as key support points. Although the station attendants (overseers) were under the authority of post offices, they independently managed operations and relied on station-generated income. This arrangement was cost-effective for the state, allowing it to minimize expenses on postal institutions. The Russian government consistently worked to improve postal communication, and the system was subject to ongoing changes. However, despite some positive developments, both the Russian Empire and the postal system in Semirechye lagged behind European standards of postal transport.